PROFIL PENYESUAIAN DIRI SISWA DI SMP PEMBANGUNAN LABORATORIUM UNP PADANG - SURYADI SURYADI; CITRA IMELDA USMAN (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2018)
This research is based on the researcher's concern to the students who have not been able to adapt themselves in the school which is seen from the adjustment with the school rules, teachers, peers and facilities and infrastructure in the school. As students move from elementary school to junior high school they find it difficult to adapt. Data on student conformity is obtained through observation and interview.This study aims to describe students' self-adjustment in school. The sample in this study amounted to 210 students. This research is a quantitative descriptive research. The results of this study indicate that students' self adjustment is generally categorized as good. Furthermore, based on the adjustment indicator with good rules, the indicators of adjustment with the teacher is good, adjustment indicators with peers are good and adjustment indicators based on facilities and infrastructure are also good.